PERLAKUAN AKUNTANSI TERHADAP PENGELOLAAN LIMBAH KLINIK RAWAT INAP NU IBNU SINA DAMPIT (Studi Kasus Pada Klinik Rawat Inap NU Ibnu Sina Dampit Tahun 2022) - Ahmad Alvin Ahludz Dzikrillah; Anik Malikah; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
The state of the Covid-19 pandemic that has made all elements truly a very heavy and serious challenge to the whole world. The indirect impact that must be faced is the waste of health services. The Klinik Rawat Inap NU Ibnu Sina Dampit is one of the health service providers during the Covid-19 pandemic which has to face problems regarding waste as well. The purpose of this study was to evaluate and find out about the accounting treatment of waste management at the Klinik Rawat Inap NU Ibnu Sina Dampit with PSAK concerning costs, recognition, definition, valuation or measurement, as well as disclosure and presentation in financial statements. The use of this research method is to use a comparative descriptive method with this type of qualitative research. The data collection methods used in this study were interviews, documentation, and observations. All primary data used are the results of interviews with the head of the environmental health installation and for secondary data obtained from the financial staff of the Klinik Rawat Inap NU Ibnu Sina Dampit. This study found the results at the Klinik Rawat Inap NU Ibnu Sina Dampit that there was no separation, disclosure, and presentation specifically for the waste generated, but the cost and measurement aspects can be seen in the financial statements of the results of collaboration with third parties concerned, namely the Environmental Management of Malang Regency.Keywords: PSAK 18, Covid-19, Medical Waste